Generational Differences of Technology Entrepreneurial Leadership; Comparative Case Studies of Tourism and Hospitality Industry - Tomy Andrianto; Eko Susanto (Journal of Business Management Education (JBME), 2023)
This research aims to understand the differences and similarities between generations who become technological entrepreneurs, especially in the tourism industry. The generation discussed combines Generation Y and Z with Generation X and baby boomers. A phenomenological approach used comparative case studies and content analysis to process primary and secondary data. This research resulted in the fact that there are fundamental differences in the profiles and personalities of the two generations combined, such as educational background, professional experience, and preferences for formal skills between generations. However, there are also generational similarities, namely, finances, style, and character. There are three groupings based on the similarities of this research, namely the "predecessor" group as the first group, then the "present" group, and the "future" group. This research also reveals that the most important aspect is adaptation to challenging situations related to business models. Technology is not an obstacle but a tool to uncover the mysteries of the future, and those who can optimize it will become future leaders.